Aromaterapi Menurunkan Tingkat Nyeri Kepala Penderita Migren - Joni Haryanto; Kusnanto Kusnanto; Ira Suarilah; Ratna Puji Priyanti (Jurnal Ners, 2007)
Introduction: Migraine was one of the headache type which is often griped by most of young woman. Migraine could influence activity, degrading work productivity, bothering work, family and social life, and there was possibility to loose job opportunity and decreased salary. Aromatherapy was one of the alternative that could be taken to decrease the migraine pain. Aromatherapy was trust directly influent brain to changed someone’s emotion and mood. The objective of this study was to analyze the effect of aromatherapy to decrease the migraine pain. Method: This study was used a quasy-eksperimental design. There were 12 respondents who met the inclusion criteria, divided into treatment and control group. The independent variable was giving aromatherapy and the dependent variable was decrease pain level of migraine patients. Data were obtained by using observation and questionare, then analyzed by using Wilcoxon Signed Rank Test with level of significanceα ≤0.05, Mann-Withney U Test with level of significance <0.05. Result: The result showed that giving aromatherapy had strong influence to decrease pain level of migraine patients, with the result of statistical test had same significant  level p=0.014. The result showed that there was differences of post test pain level post test between treatment and control group, with the result of statistical test had same significant  level p=0.011. Discussion:  It can be concluded that giving aromatherapy could decrease pain level of migraine patient. Recommendation for the nurses and other health profession to use aromatherapy as alternative medication of migraine naturally. Further studies need to be conducted regarding aromatherapy in decreasing pain level of migraine patients to help assisted curing prosess.